Customer Relationship Management (CRM) and Customer Retention in Nigeria Banking Industry: A Strategic Standpoint - Akintunde, Olufemi Atanda; Akaighe, Godbless Onoriode (Journal of Marketing Development and Competitiveness, 2016)
The study investigates CRM and Customer retention in the Nigerian banking industry. Five (5) research objectives and hypotheses were developed for the study. Quantitative research method was adopted and sample size of 420 relationship management personnel and marketers were surveyed using stratified random sampling technique. The result establishes a positive significant relationship between CRM and customer retention. Also, CRM in the banking industry is imperative for capital adequacy, earnings, profitability and liquidity. The ‘know your customer’ (KYC) and the ‘bank verification number’ (BVN) programmes should be fully integrated in the customer data base for effective relationship management and customer retention.